Preparation method and application of high-capacity positive electrode material for improving two-phase uniformity
Through sand grinding and spray granulation technology, the problem of poor uniformity of the two phases in lithium-rich manganese-based batteries is solved, the electrochemical performance and energy density of the battery are improved, and more efficient charging and discharge performance is achieved.
Patent Information
- Application Number
- CN202411140408.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-20
- Publication Date
- 2025-01-10
AI Technical Summary
Lithium-rich manganese-based batteries have poor primary efficiency, poor circulation performance, loose material structure and segregation of manganese content, which affects the electrochemical performance.
Sand grinding and spray granulation technology are used to form a high spherical and uniformly distributed lithium-rich manganese-based positive electrode material through pulverization and secondary calcination to avoid manganese segregation and structural collapse.
It significantly improves the spherical and cyclic properties of the material, improves the volume energy density and charge and discharge efficiency of the battery, and ensures the uniformity of the two-phase distribution and electrochemical performance.
Smart Images

Figure BDA0005000616770000071 
Figure BDA0005000616770000081 
Figure HDA0005000616780000011
Abstract
Description
Technical Field
[0001] The present invention relates to a preparation method and application of a high-capacity positive electrode material with improved two-phase uniformity, and relates to H01M, and specifically to the field of a method or device for directly converting chemical energy into electrical energy. Background Art
[0002] Lithium-rich manganese-based cathode materials have attracted widespread attention due to their high energy density, excellent thermal stability, and low production cost advantages. However, their inevitable low first efficiency, low compaction density, and poor cycle performance also limit the development of lithium-rich manganese-based batteries. The lithium-rich manganese-based precursors of the hydroxide system have a high manganese content, poor particle sphericity, and low first efficiency after calcination; the carbonate system has good sphericity, but the material structure is loose and the tap density is low. In addition, both the hydroxide system and the carbonate system are accompanied by segregation of manganese content, and the element distribution of the precursor material particles is uneven, which affects the uniformity of the distribution of the two phases (Li2MnO3 phase and LiMO2 phase) of the lithium-rich manganese-based material after calcination. Therefore, it is very important to develop a process to improve the uniformity of the two phases of lithium-rich manganese-based cathode materials and optimize the comprehensive electrochemical performance of lithium-rich manganese-based cathode materials.
[0003] Chinese invention patent CN104752709B discloses a method for preparing a lithium-rich manganese-based positive electrode material hydroxide precursor, which adopts a hydroxide coprecipitation method to prepare a lithium-rich solid solution positive electrode material precursor, and controls the preparation temperature to achieve the regulation of the precursor crystal growth, thereby generating a dense spherical lithium-rich solid solution positive electrode material precursor. However, the battery capacity is not high, and the electrochemical performance is not significantly improved. Chinese invention patent CN109686967A discloses a lithium-rich manganese-based positive electrode material and a preparation method thereof, which obtains a lithium-rich manganese-based lithium ion positive electrode material with a three-layer core-shell spherical structure by preparing a nickel cobalt manganese carbonate precursor having a stable interface structure with three layers of different metal ion concentrations. However, the sphericity of the formed particles is not high, and the tap density is low. Summary of the invention
[0004] In order to improve the sphericity of material particles and optimize the electrochemical performance of the battery during use, the first aspect of the present invention provides a method for preparing a high-capacity positive electrode material with improved two-phase uniformity, comprising the following steps:
[0005] S1 prepares precursors;
[0006] S2 primary calcination: the precursor, lithium salt and additive are mixed, air is introduced into the calcination in a box furnace, and after sintering, they are crushed and sieved to obtain the initial product of lithium-rich manganese-based positive electrode material;
[0007] S3 sanding spray: The initial lithium-rich manganese-based cathode material is mixed with water to form a suspension, which is sanded with a sand mill and then sprayed and granulated with a spray device for drying;
[0008] S4 secondary roasting.
[0009] As a preferred embodiment, the preparation process of the precursor includes the following steps: preparing Ni, Co, and Mn into a mixed salt solution, then adding a strong alkaline solution of sodium hydroxide, and adding ammonia water as a complexing agent, and passing nitrogen protection, controlling the reaction temperature, reaction time, and pH to carry out a co-precipitation reaction, and then filtering the precipitate, washing, and drying to obtain a lithium-rich manganese-based precursor.
[0010] As a preferred embodiment, the salt solution of Ni, Co, and Mn is a mixed salt solution of NiSO4·6H2O, CoSO4·7H2O, and MnSO4·H2O.
[0011] As a preferred embodiment, the concentration of the mixed salt solution is 1.2-2.8 mol / L, the concentration of the sodium hydroxide strong base solution is 2-10 mol / L, and the concentration of the ammonia water is 0-6 mol / L.
[0012] As a preferred embodiment, the concentration of the mixed salt solution is 2.7 mol / L, the concentration of the sodium hydroxide strong alkali solution is 7 mol / L, and the concentration of the ammonia water is 3 mol / L.
[0013] As a preferred embodiment, the reaction temperature of step S1 is 30-70°C, the reaction time is 20-45h, and the reaction pH is 10-12.
[0014] As a preferred embodiment, the reaction temperature of step S1 is 50° C., the reaction time is 40 h, and the reaction pH is 11.2.
[0015] As a preferred embodiment, the precursor is a lithium-rich manganese-based precursor, and the chemical formula of the lithium-rich manganese-based precursor is Ni x Co y Mn z (OH)2, where x+y+z=1, 0.2<x<0.5, 0.5<z<0.8, y=1-xz.
[0016] As a preferred embodiment, the molar ratio of Ni, Co and Mn is x:y:z.
[0017] As a preferred embodiment, the molar ratio of Ni, Co and Mn is 0.3:0.1:0.6.
[0018] As a preferred embodiment, the additive in step S2 is a metal oxide, and the metal oxide is selected from one or a combination of ZrO2, Al2O3, WO3, CeO2, MoO3, Sb2O3.
[0019] The present application can stabilize the crystal structure by doping metal oxide elements, thereby avoiding the problems of rapid structural collapse, low cycle performance and poor storage during the cycle process.
[0020] As a preferred embodiment, the lithium salt is selected from one or a combination of Li2CO3 and LiOH.
[0021] As a preferred embodiment, the molar amount of the precursor exceeds the molar amount of the lithium salt by 0-20%, and the added amount of the additive is 0.1%-0.5% of the mass of the precursor.
[0022] As a preferred embodiment, the molar amount of the precursor exceeds 9% of the molar amount of the lithium salt, and the added amount of the additive is 0.2% of the mass of the precursor.
[0023] As a preferred embodiment, the primary calcination temperature is 800-1000° C., and the primary calcination time is 15-25 hours.
[0024] As a preferred embodiment, the primary calcination temperature is 850-950°C, and the primary calcination time is 15-18h.
[0025] As a preferred embodiment, the primary calcination temperature is 850° C. and the primary calcination time is 18 hours.
[0026] As a preferred embodiment, the solid content of the suspension in step S3 is 20wt%-40wt%, and the sand grinding time is 6-10h.
[0027] As a preferred embodiment, the solid content of the suspension in step S3 is 30wt%-40wt%, and the sand grinding time is 6-9h.
[0028] As a preferred embodiment, the solid content of the suspension in step S3 is 30 wt % and the sand grinding time is 6 h.
[0029] As a preferred embodiment, the spraying method in step S3 is two-fluid spraying, the spray drying temperature is 110-130° C., and the granulation particle size is 5-10 μm.
[0030] As a preferred embodiment, the spray drying temperature is 110-120°C, and the granulation particle size is 6-9 μm.
[0031] As a preferred embodiment, the spray drying temperature is 120°C.
[0032] As a preferred embodiment, the secondary calcination temperature is 900-1050° C., and the calcination time is 10-20 hours.
[0033] As a preferred embodiment, the secondary calcination temperature is 960-1000° C., and the calcination time is 10-12 hours.
[0034] As a preferred implementation manner, the secondary calcination temperature is 960° C. and the calcination time is 12 hours.
[0035] During the experiment, the applicant found that due to the high manganese content in the lithium-rich manganese-based positive electrode material, accompanied by the segregation of the manganese content, the distribution of nickel and cobalt phases in the positive electrode material will be uneven, and the uneven distribution of particle elements will lead to poor sphericity of the material particles. The decrease in tap density leads to loose material structure, which affects the volume energy density of the battery positive electrode, and during the cycle, it is easy to cause rapid structural collapse and low cycle performance. The applicant sand-milled the lithium-rich manganese-based precursor, and used a spray equipment to spray granulate and dry it with two fluids, and then calcined it twice. The obtained lithium-rich manganese-based positive electrode material has high structural sphericity and high spherical distribution uniformity. The particle size distribution of the material particles is concentrated, D50 is 5-10μm, and the formed positive electrode material has a high tap density, which improves the distribution uniformity of the material particles, and improves the charging and discharging efficiency and energy retention efficiency. The reason is that after the two-fluid spray and secondary calcination, the elements agglomerate, achieve complete nano-ization, and the crystal phase will not segregate, thereby improving the electrochemical performance of the battery.
[0036] A second aspect of the present invention provides a lithium-rich manganese-based positive electrode material, which is prepared by the method for preparing a high-capacity positive electrode material with improved two-phase uniformity described in the present invention.
[0037] As a preferred embodiment, the chemical formula of the lithium-rich manganese-based positive electrode material is mLi2MnO3·(1-m)LiNi 0.5 Mn 0.5 O2, where 0<m<0.6.
[0038] Compared with the prior art, the present invention has the following beneficial effects:
[0039] (1) The present invention provides a method for preparing a high-capacity positive electrode material with improved two-phase uniformity. The uniformity of the two-phase distribution is improved by sand grinding and particle nano-sizing. The sample capacity and the first efficiency are greatly improved, and the cycle performance of the material is also improved.
[0040] (2) The method for preparing a high-capacity positive electrode material with improved two-phase uniformity of the present invention greatly improves the sphericity of the material particles through spray regranulation, thereby improving the volume energy density of the battery material.
[0041] (3) The method for preparing a high-capacity positive electrode material with improved two-phase uniformity of the present invention comprises sand grinding after primary calcination, agglomeration after secondary calcination, and complete nano-crystallization, and the crystal phase after crystallization will not be segregated.
[0042] (4) The method for preparing a high-capacity positive electrode material with improved two-phase uniformity of the present invention is based on a hydroxide system. On the basis of a high manganese content, the sphericity of the precursor is not affected, and the sphericity of the positive electrode material particles is also relatively high, thereby enabling the battery to have a higher volume energy density when used.
[0043] (5) The method for preparing a high-capacity positive electrode material with improved two-phase uniformity of the present invention makes the Li2MnO3 and LiMO2 two-phases evenly distributed, and the Ni / Co / Mn elements evenly distributed, thereby avoiding the accumulation of Li2MnO3 phases in blocks, which causes the structure to collapse rapidly during the cycle, resulting in low cycle performance and poor storage. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] Figure 1 This is an electron microscope image of the overall structure of the high-capacity positive electrode material prepared in Example 1;
[0045] Figure 2 This is an electron microscope image of the overall structure of the high-capacity positive electrode material prepared in Example 2;
[0046] Figure 3 The electron microscope image of the overall structure of the high-capacity positive electrode material prepared in Comparative Example 1;
[0047] Figure 4 This is an electron microscope image of the surface structure of the high-capacity positive electrode material prepared in Example 1;
[0048] Figure 5 This is an electron microscope image of the surface structure of the high-capacity positive electrode material prepared in Example 2;
[0049] Figure 6 The electron microscope image of the surface structure of the high-capacity positive electrode material prepared in Comparative Example 1;
[0050] Figure 7 Comparison of charge and discharge curves of batteries made from the positive electrode materials prepared in Examples 1 and 2 and Comparative Example 1;
[0051] Figure 8 XRD comparison spectra of the positive electrode materials prepared in Examples 1, 2 and Comparative Example 1;
[0052] Fig. 9 This is a comparison chart of the cycle capacity retention rate of batteries made from the positive electrode materials prepared in Examples 1, 2 and Comparative Example 1. DETAILED DESCRIPTION
[0053] Example 1
[0054] A method for preparing a high-capacity positive electrode material with improved two-phase uniformity comprises the following steps:
[0055] S1: Preparing the precursor: Ni, Co, and Mn are prepared into a mixed salt solution, and then a sodium hydroxide strong base solution is added, and ammonia water is added as a complexing agent, and nitrogen is introduced for protection, and the reaction temperature, reaction time, and pH are controlled to perform a co-precipitation reaction, and then the precipitate is filtered, washed, and dried to obtain a lithium-rich manganese-based precursor. ;
[0056] S2 primary calcination: the precursor, lithium salt and additive are mixed, air is introduced into the calcination in a box furnace, and after sintering, the mixture is crushed and passed through a 325-mesh sieve to obtain a primary product of lithium-rich manganese-based positive electrode material;
[0057] S3 sanding spray: The initial lithium-rich manganese-based cathode material is mixed with water to form a suspension, which is sanded with a sand mill and then sprayed and granulated with a spray device for drying;
[0058] S4 secondary calcination: secondary calcination of the dried lithium-rich manganese-based positive electrode material to obtain a lithium-rich manganese-based positive electrode material.
[0059] The salt solution of Ni, Co and Mn is a mixed salt solution of NiSO4·6H2O, CoSO4·7H2O and MnSO4·H2O. The concentration of the mixed salt solution is 2.7 mol / L. The concentration of the sodium hydroxide strong alkali solution is 7 mol / L, and the concentration of the ammonia water is 3 mol / L.
[0060] The reaction temperature of step S1 is 50° C., the reaction time is 40 h, and the reaction pH is 11.2.
[0061] The molar ratio of Ni, Co and Mn is 0.3:0.1:0.6. The precursor is a lithium-rich manganese-based precursor, and the chemical formula of the lithium-rich manganese-based precursor is Ni 0.3 Co 0.1 Mn 0.6 (OH)2.
[0062] The lithium salt is Li2CO3, the additive is ZrO2, the molar amount of the precursor exceeds 9% of the molar amount of the lithium salt, and the added amount of the additive is 0.2% of the mass of the precursor.
[0063] The temperature of the first calcination is 850° C., and the time of the first calcination is 18 hours.
[0064] The solid content of the suspension in step S3 is 30 wt % and the sand grinding time is 6 h.
[0065] The spraying method in step S3 is two-fluid spraying, and the spray drying temperature is 120°C.
[0066] The secondary calcination temperature is 960° C. and the calcination time is 12 h.
[0067] Electron micrographs see Figure 1 , 4. From the overall structure, it can be seen that the particles have a high degree of sphericity and there are no sharp edges on the surface.
[0068] Example 2
[0069] A method for preparing a high-capacity positive electrode material with improved two-phase uniformity comprises the following steps:
[0070] S1: Preparing the precursor: Ni, Co, and Mn are prepared into a mixed salt solution, and then a sodium hydroxide strong base solution is added, and ammonia water is added as a complexing agent, and nitrogen is introduced for protection, and the reaction temperature, reaction time, and pH are controlled to perform a co-precipitation reaction, and then the precipitate is filtered, washed, and dried to obtain a lithium-rich manganese-based precursor. ;
[0071] S2 primary calcination: the precursor, lithium salt and additive are mixed, air is introduced into the calcination in a box furnace, and after sintering, the mixture is crushed and passed through a 325-mesh sieve to obtain a primary product of lithium-rich manganese-based positive electrode material;
[0072] S3 sanding spray: The initial lithium-rich manganese-based cathode material is mixed with water to form a suspension, which is sanded with a sand mill and then sprayed and granulated with a spray device for drying;
[0073] S4 secondary calcination: secondary calcination of the dried lithium-rich manganese-based positive electrode material to obtain a lithium-rich manganese-based positive electrode material.
[0074] The salt solution of Ni, Co and Mn is a mixed salt solution of NiSO4·6H2O, CoSO4·7H2O and MnSO4·H2O. The concentration of the mixed salt solution is 2.7 mol / L. The concentration of the sodium hydroxide strong alkali solution is 7 mol / L, and the concentration of the ammonia water is 3 mol / L.
[0075] The reaction temperature of step S1 is 50° C., the reaction time is 40 h, and the reaction pH is 11.2.
[0076] The molar ratio of Ni, Co and Mn is 0.3:0.1:0.6. The precursor is a lithium-rich manganese-based precursor, and the chemical formula of the lithium-rich manganese-based precursor is Ni 0.3 Co 0.1 Mn 0.6 (OH)2.
[0077] The lithium salt is Li2CO3, the additive is Al2O3, the molar amount of the precursor exceeds 9% of the molar amount of the lithium salt, and the added amount of the additive is 0.2% of the mass of the precursor.
[0078] The temperature of the first calcination is 950° C., and the time of the first calcination is 15 hours.
[0079] The solid content of the suspension in step S3 is 30 wt % and the sand grinding time is 9 h.
[0080] The spraying method in step S3 is two-fluid spraying, and the spray drying temperature is 110°C.
[0081] The secondary calcination temperature is 1000° C. and the calcination time is 12 hours.
[0082] Electron micrographs see Figure 2 , 5. From the overall structure, it can be seen that the particles have a high degree of sphericity and no sharp edges on the surface.
[0083] Comparative Example 1
[0084] A method for preparing a high-capacity positive electrode material with improved two-phase uniformity comprises the following steps:
[0085] S1: Preparing the precursor: Ni, Co, and Mn are prepared into a mixed salt solution, and then a sodium hydroxide strong base solution is added, and ammonia water is added as a complexing agent, and nitrogen is introduced for protection, and the reaction temperature, reaction time, and pH are controlled to perform a co-precipitation reaction, and then the precipitate is filtered, washed, and dried to obtain a lithium-rich manganese-based precursor. ;
[0086] S2 primary calcination: the precursor, lithium salt and additive are mixed, air is introduced into the calcination in a box furnace, and after sintering, they are crushed and passed through a 325 mesh sieve to obtain a lithium-rich manganese-based positive electrode material.
[0087] The salt solution of Ni, Co and Mn is a mixed salt solution of NiSO4·6H2O, CoSO4·7H2O and MnSO4·H2O. The concentration of the mixed salt solution is 2.7 mol / L. The concentration of the sodium hydroxide strong alkali solution is 7 mol / L, and the concentration of the ammonia water is 3 mol / L.
[0088] The reaction temperature of step S1 is 50° C., the reaction time is 40 h, and the reaction pH is 11.2.
[0089] The molar ratio of Ni, Co and Mn is 0.3:0.1:0.6. The precursor is a lithium-rich manganese-based precursor, and the chemical formula of the lithium-rich manganese-based precursor is Ni 0.3 Co 0.1 Mn 0.6 (OH)2.
[0090] The lithium salt is Li2CO3, the additive is ZrO2, the molar amount of the precursor exceeds 9% of the molar amount of the lithium salt, and the added amount of the additive is 0.2% of the mass of the precursor.
[0091] The temperature of the first calcination is 850° C., and the time of the first calcination is 18 hours.
[0092] Electron micrographs see Figure 3 ,6. From the overall structure, it can be seen that the particles are almost not spherical and have obvious protrusions on the surface.
[0093] Performance Testing
[0094] The lithium-rich manganese-based positive electrode materials of Examples 1-2 and Comparative Example 1 were prepared into button batteries, and the specific capacity and initial efficiency were tested under the conditions of 2.3-4.55V, 1C=230mAh / g.
[0095] Button battery: The mass ratio of lithium-rich manganese-based positive electrode material, SP conductive agent, and PVDF binder is 92:4:4, the negative electrode uses metal lithium sheet, the diaphragm uses PP material diaphragm, the electrolyte uses carbonate as solvent and LiPF6 as solute, and is assembled into button batteries in a nitrogen environment in a glove box according to the existing method.
[0096] The test results are shown in Table 1; the charge and discharge curves are shown in Figure 7 , XRD pattern see Figure 8 , the cycle capacity retention rate is shown in Fig. 9 In the figure: a: Example 1; b: Example 2; c: Comparative Example 1.
[0097] Table 1
[0098]
[0099]
Claims
1. A method for preparing a high-capacity positive electrode material with improved two-phase uniformity, characterized in that: The following steps are involved: S1 prepares precursors; S2 primary calcination: the precursor, lithium salt and additive are mixed, air is introduced into the calcination in a box furnace, and after sintering, they are crushed and sieved to obtain the initial product of lithium-rich manganese-based positive electrode material; S3 sanding spray: The initial lithium-rich manganese-based cathode material is mixed with water to form a suspension, which is sanded with a sand mill and then sprayed and granulated with a spray device for drying; S4 secondary roasting.
2. The method for preparing a high-capacity positive electrode material with improved two-phase uniformity according to claim 1, characterized in that: The precursor is a lithium-rich manganese-based precursor, and the chemical formula of the lithium-rich manganese-based precursor is Ni x Co y Mn z (OH)2, where x+y+z=1, 0.2<x<0.5, 0.5<z<0.8, y=1-xz.
3. The method for preparing a high-capacity positive electrode material with improved two-phase uniformity according to claim 1, characterized in that: The additive in step S2 is a metal oxide, and the metal oxide is selected from one or a combination of ZrO2, Al2O3, WO3, CeO2, MoO3, Sb2O3.
4. The method for preparing a high-capacity positive electrode material with improved two-phase uniformity according to claim 1, characterized in that: The molar amount of the precursor exceeds the molar amount of the lithium salt by 0-20%, and the added amount of the additive is 0.1%-0.5% of the mass of the precursor.
5. The method for preparing a high-capacity positive electrode material with improved two-phase uniformity according to claim 1, characterized in that: The temperature of the first calcination is 800-1000° C., and the time of the first calcination is 15-25 hours.
6. The method for preparing a high-capacity positive electrode material with improved two-phase uniformity according to claim 1, characterized in that: The solid content of the suspension in step S3 is 20wt%-40wt%, and the sand grinding time is 6-10h.
7. The method for preparing a high-capacity positive electrode material with improved two-phase uniformity according to claim 1, characterized in that: In step S3, the spraying method is two-fluid spraying, the spray drying temperature is 110-130° C., and the granulation particle size is 5-10 μm.
8. The method for preparing a high-capacity positive electrode material with improved two-phase uniformity according to claim 1, characterized in that: The secondary calcination temperature is 900-1050° C., and the calcination time is 10-20 hours.
9. A lithium-rich manganese-based positive electrode material, characterized in that: The high-capacity positive electrode material is prepared by the method for preparing a high-capacity positive electrode material with improved two-phase uniformity as described in any one of claims 1 to 8.
10. The lithium-rich manganese-based positive electrode material according to claim 9, characterized in that: The lithium-rich manganese-based positive claims The chemical formula of the electrode material is mLi2MnO3·(1-m)LiNi 0.5 Mn 0.5 O2, where 0<m<0.6.
Citation Information
Patent Citations
A method for preparing a lithium-rich manganese-based cathode material hydroxide precursor
CN104752709B
Lithium-enriched manganese-based positive electrode material and preparation method thereof
CN109686967A